Theoretical studies of the local structures and EPR parameters for Cu²⁺ center in Cd₂(NH₄)₂(SO₄)₃ single crystal - Li, Ch.-Y.; Chen, L.-B.; Mao, J.-J.; Zheng, X.-M. (Condensed Matter Physics, 2015)
The electron paramagnetic resonance (EPR) parameters (g factors gi and the hyperfine structure constants Ai, i = x, y, z) are interpreted by using the perturbation formulae for a 3d⁹ ion in rhombically (D₂h) elongated octahedra. In the calculated formulae, the crystal field parameters are set up from the superposition model, and the contribution to the EPR parameters from the admixture of d-orbitals in the ground state wave function of the Cu²⁺ ion was taken into account. Based on the calculation, local structural parameters of the impurity Cu²⁺ center in Cd₂(NH₄)₂(SO₄)₃ (CAS) crystal were obtained (i.e., Rx ≈ 2.05 Å, Ry ≈ 1.91Å, Rz ≈ 2.32 Å). The theoretical EPR parameters based on the above Cu²⁺-O²⁻ bond lengths in CAS crystal show a good agreement with the observed values. The results are discussed. Параметри електронного парамагнiтного резонансу (ЕПР) (g -фактори gi
i константи надтонкої структури
Ai
, i = x, y, z) iнтерпретуються за допомогою формули збурень для iона 3d⁹
у ромбiчно (D₂h) видовженому восьмиграннику. У формулах параметри кристалiчного поля встановлюються згiдно суперпозицiйної
моделi, де враховується внесок у параметри ЕПР вiд домiшування d-орбiталей в основному станi хвильової функцiї Cu²⁺. На основi обчислень отримано локальнi структурнi параметри домiшки центру Cu²⁺ у
кристалi Cd₂(NH₄)₂(SO₄)₃ (CAS) (тобто, Rx ≈ 2.05 A, ˚ Ry ≈ 1.91 A, ˚ Rz ≈ 2.32 A). ˚ Теоретичнi параметри ЕПР,
що базуються на вищезгаданих довжинах Cu²⁺–O
²⁻ зв’язку у CAS кристалi, демонструють хороше узгодження з спостережуваними значеннями. Результати дослiджень обговорюються.